Sobrevivencia de Eucheira socialis westwoodi Beutelspacher (Lepidoptera:Pieridae) en la reserva de la Biosfera "La Michilía", Durango, México. - Díaz Batres, Ma. Eugenia (Instituto de Ecología, A.C., 1991)
The survival of the Eucheira socialis westwoodi (Lep. Pieridae) was studied at "la Michilia" Biosphere Reserve, Durango, México. Two nest groups were observed under natural conditions. The first one was composed of four clutches and were observed during their development in one year, and the second one by síxteen nests used for estimating pupal exuvias and dead pupas by the end of the cycle. Survival of group I was 5% and group II was 11 %. Fauna associated to nests of this butterfly was identified and quantified. The most common were: Phoridae (Díptera) 49.8%, Torymidae (Hymenoptera) 15.9%, Alleculidae (Coleóptera) 9.9%, and Staphylinidae (Coleoptera) 8.5%.